1991
DOI: 10.1172/jci115029
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the functional capacity of human neonatal lymphocytes.

Abstract: Neonatal T cell-B cell collaboration was investigated utilizing a system of T cell-dependent polyclonal B cell activation and Ig secretion. In (J. Clin. Invest. 1991. 87:545-553.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 50 publications
(27 reference statements)
2
46
0
4
Order By: Relevance
“…Taken together, these data suggest that an impaired induction of hBD2 as part of an immature intestinal innate immune defense may play an important role particularly in NEC as ELBW infants with an increase in fecal hBD2 concentrations showed a much more moderate course of the disease. This hypothesis is in line with several reports demonstrating an impaired innate and adaptive immune response in ELBW infants (1,2,20). As hBD2 has been shown to be at least partly regulated by TLR4 and MD2 signaling (10,21), we investigated expression levels of these receptor molecules during and 14 wk after NEC in the two surviving patients.…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 80%
“…Taken together, these data suggest that an impaired induction of hBD2 as part of an immature intestinal innate immune defense may play an important role particularly in NEC as ELBW infants with an increase in fecal hBD2 concentrations showed a much more moderate course of the disease. This hypothesis is in line with several reports demonstrating an impaired innate and adaptive immune response in ELBW infants (1,2,20). As hBD2 has been shown to be at least partly regulated by TLR4 and MD2 signaling (10,21), we investigated expression levels of these receptor molecules during and 14 wk after NEC in the two surviving patients.…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 80%
“…5) and B lymphoblastoid (data not shown) cell lines transfected with CD1c induced DN T cells to produce cytokines, neonatal B cells did not stimulate detectable levels of cytokines from DN T cells, perhaps due to a reduced level of costimulation. Previous studies have shown that neonatal B cells produce IgM but only low levels of IgG in response to agonistic signals that induce adult B cells (29) (Fig. 7A).…”
Section: Cd1c-directly Reactive T Cells Of Sle Patients Induce Igg Absmentioning
confidence: 80%
“…In this study we analyze the development of the IgG repertoire in preterm and term neonates during a postconceptional age of 24 to 68 wk, i.e., during the time period when neonatal immunocompetence gradually increases from the "immunodeficiency of extreme prematurity" to the ability to produce Abs against various groups of Ags (23,24). By comparing preterm and term neonates at an identical postconceptional age but after different environmental exposures, we could discern changes that are triggered by preterm birth from changes that occur during physiologic intrauterine development.…”
Section: Discussionmentioning
confidence: 99%
“…1). In vitro, when appropriate T cell help and an appropriate cytokine milieu are artificially provided, cord blood B cells of preterm infants are able to undergo class switch more efficiently than they apparently do in vivo (23,42).…”
Section: Discussionmentioning
confidence: 99%